Efficacy of electronic identification in beef cattle - Spell, A.R.; Utter, S.D.; Corah, L.R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
To evaluate the potential of using electronic implants (transponders) for maintaining identity from birth to slaughter, calves born and implanted in Montana were followed through the feedlot phase to their ultimate slaughter at commercial packing plants. At spring branding, 138 calves were implanted with electronic identification transponders positioned underneath the scutiform cartilage at the base of the ear. Four steers died prior to weaning. After weaning, 109 steers were transported to a commercial feedlot i n Kansas (group 1) and the remaining 25 steers (group 2) were maintained at the Montana ranch for 1 year and then placed in a commercial feedlot in Colorado. Following the two feeding periods, steers were slaughtered at commercial packing plants in Colorado or Kansas under Food Safety Inspection Service authority. From implanting to weaning (156 days), retention was 100%, and 98.5% of the implants remained operable. Of the 106 steers that survived in the first group, implant retention was 98.1%, and all implants were recovered at slaughter. Of the 25 steers in the second group, identity was maintained on 20 steers up to slaughter, 661 days postbranding. This study illustrated that electronic implants will maintain identity on a very high percentage of cattle from birth to slaughter and that the implants can be recovered at the time of slaughter.
Keywords: Beef; Electronic identification; Identification system